Proteins and lipids of the blood serum and the liver of Antarctic fishes - V. Voitsitsky; S. Khyzhnyk; A. Pavlyk; L. Manilo (Ukrainian Antarctic Journal, 2008)
It was realized the comparative analysis of protein and lipid contents of the blood serum and the liver of the different species of antarctic fishes. The materials were collected during the 9-th and 11-th Ukrainian antarctic expedition in Argentine islands region. We have defined the presence of the low-molecular protein (glycoprotein) with molecular weight 13kDa in N. coriiceps, P. charcoti, C. aceratus and its absence in T. bernacchii and G. gibberifrons. It was determined that Antarctic fishes is characterized by the features of lipids’ component of the blood serum and liver cells, which may determine the features of its metabolism. Established differences of protein and lipid components of the different species of Antarctic fishes may be interpreted as the species difference, also as the different ways of adaptation to low temperature conditions.